The Effect of the UbD-Based Problem Based Learning Model on the Critical Thinking Skills of Grade IV Students in IPAS Subject at Elementary School - Aristanti, Anastasya Putri; Fatayan, Arum (Mimbar Sekolah Dasar, 2024)
The ability to think critically in the 21st century is a skill that must be possessed by every individual. This study, uses a UbD-based problem-based learning model with a conventional learning model to see which learning model has more influence on the critical thinking ability of grade IV students in science subjects. The UbD approach was chosen to be a supporter in the implementation of the problem-based learning model because it is considered to have the same goal, which is to provide students with a deep understanding to encourage students to be more active in the learning process which also encourages students to think critically. The research method used in this study is quasi-experimental. Researchers used all students in class IV A totaling 25 students as the control class and IV B totaling 32 students as the experimental class. The experimental group was given UbD-based problem-based learning model treatment while the control class was given conventional model treatment. The results showed that the experimental class with UbD-based problem-based learning model treatment was superior to its post-test value compared to the control class. The findings of this study can help teachers or instructors to find a suitable learning model that has a deep impact on students so that students can improve their critical thinking skills, which is a must-have ability in the 21st century.